How Heterodox Economics Lost its Way. Issue 3 (3rd July 2021) - Potts, Jason
Abstract: Hodgson's recent book Is there a Future for Heterodox Economics? presents a serious critical analysis of the development of heterodox economics and offers diagnosis of why it has mostly failed to attain its early revolutionary hopes, but instead has become something of an intellectual backwater. Hodgson proposes several possible pathways back into the mainstream. I argue here in support of Hodgson's diagnosis but propose a specific way forward with heterodox economics as the study of the evolution of economic rules and focused on analysis of a digital economy.